Phytochemical Profile and Anticancer Activity from Medicinal Plants Against Melanoma Skin Cancer: A Review - Adryan Fristiohady; Rathapon Asasutjarit; La Ode Muh. Julian Purnama; Sewan Theeramunkong; Wirhamsah Al-Ramadan; Lidya Agriningsih Haruna; Nur Syifa Rahmatika; Syarul Nataqain Baharum; I. Sahidin (Indonesian Journal of Science and Technology, 2022)
Melanoma skin cancer is a malignant melanocyte tumor considered the most invasive and dangerous skin cancer, with an average five-year survival rate of less than 5% after metastasis. Thus, a new strategy for preventing and treating cancer from the natural product is required. Medicinal plants are the potential as an alternative against cancer. This review article aims to determine natural products from medicinal plants which have the potential as an anticancer in melanoma skin cancer in vitro and in vivo. 40 plants have been selected based on the selection criteria for anticancer compounds. In vitro studies showed that the plant can reduce cell viability through cell cycle inhibition and apoptosis induction and inhibit angiogenesis, invasion, and metastasis in human melanoma skin cancer. Therefore, further research is required to explore more plants, especially medicinal plants, their active compounds, and the mechanism of anticancer action to be used as standard herbal medicines.